THE PORTRAIT OF INDONESIAN CULTURE THROUGH AN ANIMATED FILM “SI ENTONG” - Lambok Hermanto Sihombing; Puji Lestari (Universitas Galuh, 2022)
Indonesia is a multicultural nation home to many different tribes, religions, languages, and traditions. Each region in Indonesia has a unique variety of characteristics. Some of the characteristics can be seen through the traditional dress and traditional games. This study discusses the portrait of Indonesian culture through an animated movie “Si Entong”. This research focuses on findings of the scene that portrays the characters from each region in Indonesia and traditional games in “Si Entong”. In this study, the researchers applied the qualitative method to analyze the data. In order to aid the authors doing this analysis, Mise En Scene approach from Manon de Reeper and Theory of Representation from Stuart Hall are used for this study. Therefore, the result of this research shows the representation of Indonesian culture that can be seen from the traditional dress that the characters wear and the traditional game they play in the movie.